UPR, autophagy, and mitochondria crosstalk underlies the ER stress response. Issue 3 (March 2015) - Senft, Daniela; Ronai, Ze'ev A.
Highlights Autophagy and UPR interaction underlies ERS response outcomes. ERS modulates mitochondrial biogenesis and function. Ubiquitin ligases fine-tune the ERS response.